Current approach to the treatment of chronic myeloid leukaemia. (April 2017) - Pasic, Ivan; Lipton, Jeffrey H.
Highlights: There are many successful options for treating chronic myeloid leukaemia. Currently five tyrosine kinase inhibitors are available. Different side effect profiles can be used to integrate therapy for patients with co-morbidities. Survival of newly diagnosed CML patients with chronic phase disease is nearly that of age-matched controls. Abstract: Of all the cancers, chronic myeloid leukaemia (CML) has witnessed the most rapid evolution of the therapeutic milieu in recent decades. The introduction of tyrosine kinase inhibitors (TKIs) as a therapeutic option has profoundly changed patient experience and outcome. The availability of multiple new highly effective therapies has increasingly underscored the importance of a good understanding of the underlying pathophysiological basis in CML, as well as patient-specific factors in choosing the right treatment for every individual. The treatment of CML has migrated in many jurisdictions from the office of a highly specialized malignant hematologist to the general hematologist or even a general practitioner. The goal of this review is to offer an overview of the modern approach to the treatment of CML, with an emphasis on chronic phase (CP) CML, including both TKI-based therapies such as imatinib, dasatinib, nilotinib, bosutinib and ponatinib, and non-TKI medications, such as omacetaxine. We discuss evidence behind each drug, most common and material adverse reactions and outline how this information can be used in selecting the right drug for the right patient. We also discuss evidence as it relates to other therapies, including stem cell transplant (SCT), and patients in accelerated (AP) and blastic phase (BP).